Broken eaudiobook - Slaughter, Karin (Will Trent, 2020)
Don't miss the next Will Trent thriller, This Is Why We Lied, coming this August! WATCH WILL TRENT ON ABC! NEW YORK TIMES BESTSELLER "This chilling mystery is just begging to be read in one sitting."—Cosmopolitan Broken features the return of New York Times bestselling author Karin Slaughter's most compelling characters and introduces memorable new ones in a tale of corruption, murder, and confrontation that will leave more than one life destroyed . . . When Special Agent Will Trent arrives in Grant County, he finds a police department determined to protect its own and far too many unanswered questions about a prisoner's death. He doesn't understand why Officer Lena Adams is hiding secrets from him. He doesn't understand her role in the death of Grant County's popular police chief. He doesn't understand why that man's widow, Dr. Sara Linton, needs him now more than ever to help her crack this case. While the police force investigates the murder of a young woman pulled from a frigid lake, Trent investigates the police force, putting pressure on Adams just when she's already about to crack. Caught between two complicated and determined women, trying to understand Linton's passionate distrust of Adams, the facts surrounding Chief Tolliver's death, and the complexities of this insular town, Trent will unleash a case filled with explosive secrets—and encounter a thin blue line that could be murderous if crossed. Spellbinding and keenly paced, Broken is Karin Slaughter at her best. Here is an unforgettable story of raw emotions, dangerous assumptions, the deadly and layered game of betrayal, and a man's determination to expose the most painful of human truths—no matter how deeply they're hidden . . . or how devastating.